(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
A new discovery of substitute of low protein but rich in nutrients wheat flour. Mocaf, low protein cassava flour, got structural changing caused by fermentation process. It occurated because lactic acid bacteria activity produced protease enzyme and cut peptide bond on protein chain in that it created dispersible lactic acid into water. In result, protein concentration was decreasing and it changed the cassava structure being porous. This porous structure enabled mocaf to be modified to triterpenoid compound to increase its nutrient content. The purposes of this study was to investigate about the influence of operating condition of fermentation to the cassava pore structure changing. Amount of triterpenoid that modified by mocaf was also studied in detail. The finding of the study showed that the fermentation time that produced expected pore structure was 12 hours and pH 4 with BIMO-CF as a bioactivator. Mocaf modified by triterpenoid was 0.457 µg/g.